2023
DOI: 10.1029/2022jc019477
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of the Land Breeze System in the Southwestern Bay of Bengal and Its Influence on Air‐Sea Interactions

Abstract: Sea surface temperature (SST) in the Bay of Bengal (BoB) plays a vital role in determining the spatio-temporal variability of Indian summer monsoon precipitation (Jiang & Li, 2011;Samanta et al., 2018;Shenoi et al., 2002). Due to the persistent occurrence of the relatively thin salt-stratified mixed layers, primarily owing to a large influx of freshwater from intense precipitation and continental rivers (Girishkumar et al., 2011;Rao and Sivakumar, 2003;Shetye et al., 1996;Thadathil et al., 2007), SST in the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The heat fluxes used in this study are also derived from ERA5 reanalysis data. Since there is no in-situ observation of surface heat fluxes (SHF) in the SETIO region, we compared the ERA5 longwave and shortwave radiation with measurements of the Research Moored Array for African-Asian-Australian Monsoon Analysis and Prediction (RAMA; Athulya et al, 2023) and achieved favorable agreement (Figure not shown). We also utilize the daily ocean temperature, mixed layer depth (MLD), and currents of 1993-2020 from the global ocean physical reanalysis product GLORYS12V1 created by Mercator Ocean with a horizontal resolution of 1 / 12 °and 50 vertical levels.…”
Section: Data Setsmentioning
confidence: 99%
“…The heat fluxes used in this study are also derived from ERA5 reanalysis data. Since there is no in-situ observation of surface heat fluxes (SHF) in the SETIO region, we compared the ERA5 longwave and shortwave radiation with measurements of the Research Moored Array for African-Asian-Australian Monsoon Analysis and Prediction (RAMA; Athulya et al, 2023) and achieved favorable agreement (Figure not shown). We also utilize the daily ocean temperature, mixed layer depth (MLD), and currents of 1993-2020 from the global ocean physical reanalysis product GLORYS12V1 created by Mercator Ocean with a horizontal resolution of 1 / 12 °and 50 vertical levels.…”
Section: Data Setsmentioning
confidence: 99%